NOCE MROŹNE W POZNANIU I ICH CYRKULACYJNE UWARUNKOWANIA - TOMCZYK, ARKADIUSZ M. (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
The main purpose of this article was to determine the pressure situations and circulation types causing the occurrence of frosty nights in Poznań in the years 1966/67–2015/16. A night was assumed to be a frosty night with a minimum temperature below –10°C. The article uses the daily values of the minimum air temperature for the period of 1966–2016 for the station in Poznań. The data was provided by the Institute of Meteorology and Water Management – National Research Institute. In the analyzed years, 10 frosty nights were recorded on average every season. Conducted studies showed a decrease in their number, although these changes were not statistically significant. The average occurrence of frosty nights was associated with the presence of a high-pressure system over Central Europe, which developed within a high-pressure ridge extending over the majority of the continent. Such a pressure situation led to the advection of continental air masses from the eastern sector.